The Effect Of Service Quality, Image, Location, And Tourist Destination Promotion On Visitor Satisfaction At Taman Wisata Iman Sitinjo In Dairi Regency - Normi, Siti; Sihite, Mislan; Sigalingging, Bahtera (Cita konsultindo, 2025)
This study aims to determine and analyze the Influence of Service Quality, Image, Location, and Promotion of Tourist Destinations on Visitor Satisfaction at Taman Wisata Iman Sitinjo in Dairi Regency. This type of research uses quantitative research. The research sample was 300 people. The data analysis method used multiple linear regression analysis. The study's results indicate that service quality partially affects visitor satisfaction at Taman Wisata Iman Sitinjo. Image partially affects visitor satisfaction at Taman Wisata Iman Sitinjo. Location partially affects visitor satisfaction at Taman Wisata Iman Sitinjo. Tourist destination promotion partially affects visitor satisfaction at Taman Wisata Iman Sitinjo. Service quality, Image, Location, and tourist destination promotion simultaneously affect visitor satisfaction at Taman Wisata Iman Sitinjo.